Potres 12.julija 2004 v zgornjem Posočju - preliminarne geološke in seizmološke značilnosti - Vidrih, Renato (Geologija, 2004)
After six years on July 12, 2004 a new earthquake shook again the most seismicdangerous part of Slovenia - the upper Soča valley. This earthquake wasabout ten times weaker then the earthquake from April 12, 1998. The earthquake was triggered at 13:04 UTC or at 15:04 according the local time. Preliminary epicentre coordinates were 46,32 N and 13,63 E. The focal depth was around 8 km deep. The earthquake with magnitude 4.9 caused the highest effects of VI to VII intensity according to EMS-98 in the settlement Čezsoča and in the surroundings of Bovec. The seismic data are preliminary and is now in the phase of supplementing. This is the reason that the most part of the paper is focused on the consequences of the earthquake on natural surroundings. The local increment of the intensity, connecting with geologicalconditions, was somewhere surprising high and exceed one degree of EMS. Many phenomena of the shallow failures released on steep slopes. Rock falls were the most frequent. Also some opening of existent and new cracks on the surface and sliding at the edge of the terraces were observed. We analysed44 rock falls, only five of them were a bit larger, so the intensity of the earthquake was to low to activate sliding of the rock blocks on deeper weak planes under the surface. We described in paper also the events of very long cracks along the edge of the terraces, which have resulted somewhere on the damage of the buildings. It was luck that the intensity of the earthquake was relatively low so the both very big landslides in Log pod Mangartom and inKoseč didn't react on the earthquake tremors.
Keywords: Posočje; poškodbe; potresi; seizmologija; Slovenia; Slovenija